(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2015)
The purpose of this paper is to analyze the phenomenon of prescription in the tax enforcement process, in parallel with the cycle of positivization of the tax obligation and in view of the legal treatment given to the institute, as well as the doctrinal and jurisprudential positions on the subject. Among the various hypotheses to be investigated, the focus is on the question of the interruption of the limitation period provided for in article 174, sole paragraph, I (in view of the filing of the tax execution and the changes introduced by Complementary Law no. 118/2005) and the question of interlocutory limitation (whether or not the executive process is suspended). The aim here is to draw a line showing how the statute of limitations has been analyzed and applied by the competent authorities and, despite the significant differences, both in doctrine and in case law, what we believe to be the most correct understanding, in terms of strict compliance with general constitutional and tax principles.